The Role of Myocardial Ischemia in the Course of Heart Failure with Preserved Ejection Fraction in Patients with Cardiorenal Metabolic Syndrome - Marushko, Yevhen Yu.; Mankovskyi, Georgii B.; Kucheriava, Mariia V. (Ukrainian Journal of Cardiovascular Surgery, 2024)
The aim. Analysis of the influence of myocardial ischemia treatment on the left ventricular diastolic function and the levels of N-terminal pro B-type natriuretic peptide (NT-proBNP) in patients with cardiorenal metabolic syndrome. Materials and methods. The study included 97 patients: 76 with confirmed coronary heart disease (CHD) (treatment group) and 21 with excluded CHD (comparison group), all of whom were examined at the Ukrainian Children’s Cardiac Center from January 1, 2023 to December 31, 2023. The main inclusion criterium for the treatment group was the presence of cardiorenal metabolic syndrome (combination of heart failure, stage ≥3A chronic kidney disease and dysglycemia in the form of type 2 diabetes or prediabetes). In 44 (57.9%) patients of the treatment group, stenosing atherosclerosis of the coronary vessels was detected and percutaneous coronary intervention was performed, while the index of coronary blood flow reserve was determined using dipyridamole test in the remaining patients, after which the diagnosis of microvascular angina was made. Microvascular dysfunction was corrected using complex therapy including nicorandil. Results. Patients with cardiorenal metabolic syndrome and CHD with normal indicators of left ventricular diastolic function at rest had disturbances in it during stress echocardiography. Patients also had elevated levels of NT-proBNP with normal left ventricular ejection fraction, indicating the presence of heart failure with preserved ejection fraction. There was a significant decrease in left ventricular diastolic dysfunction (E/e’) and serum NT-proBNP levels (p<0.05) in patients with CHD after revascularization or after correction of coronary microvascular dysfunction. The obtained data indicate the role of myocardial ischemia in the development of heart failure with preserved ejection fraction due to impaired left ventricular diastolic function. Conclusions. In CHD patients with cardiorenal metabolic syndrome, myocardial ischemia disrupts the diastolic function of the left ventricle and leads to higher levels of NT-proBNP. Restoration of myocardial blood supply by percutaneous coronary intervention in coronary artery stenoses or by medication in microvascular angina improves left ventricular diastolic function and leads to a decrease in the serum level of NT-proBNP.